ANALYSIS OF FLUORIDE CONCENTRATION IN THE WATER OF BORE-WELLS OF UMARIYA CITY , M.P., INDIA (International Journal of Food and Nutritional Sciences, 2022)
In drinking water concentration of fluoride should be in requisite amount, excess amountof fluoride in drinking water causes dental fluorosis, mottling of teeth. while lessconcentration of fluoride in ground water results in a high incidence of dental caries, inchildren’s teeth.Umariya district is famous for coal mines and stone, fluoride ions dissolved in groundwater from geological formations, so it becomes very important to analysis the fluoride inwater of bore-wells for used drinking purpose in Satna city, in this analysis evaluationof fluoride concentration done by standard analytical procedures and found 0.79 to 0.689ppm at different sampling station of umariya city during November 2017 to April 2018.